Development and Characterization on sound acoustic at photo-induced polymer foam composited at prolonged ultra-violet exposure - Taufiq Zaliran, M.; Zafiah M. Rus, Anika; Kormin, Shaharuddin; Shafiq M Azahari, M (International Journal of Engineering and Technology, 2018)
In this paper, polymer foam composites (FC) have been developed based on polyol mixed flexible crosslinker and fibre filler of Meranti Merah. 10 mm, 20 mm and 30 mm thickness of foam polymer and its composites have been use in this study. The percentage loading of wood fibre of 5%, 10%, 15% and 20% added with polymer foam is namely as polymer foam (PP) and its composites of PP5, PP10, PP15 and PP20. The sound absorption coefficient (Î±) and pore structure of the foam samples have been measure by using Impedance Tube test and Scanning Electron Microscopy (SEM). UV Weatherometer is used to examine the durability and weatherproof of its composite. The results show that the highest thickness of the highest percentage fiber filler (Pp2030) gives higher sound absorption coefficient (Î±). 0.9922 and 0.99889 which contributed from low and high frequency absorption level respectively. The smallest pores size structure was observed with highest filler loading of PP20. The higher the thickness and the higher the percentage loading of wood filler gives smaller pore structure, consequently, increased the sound absorption coefficient level. Meanwhile, the stability of polymer foam composites is high due to unchanged pore structures morphology with prolonged ultra violet exposure.Â Â